Fungal Pathogens: Emerging Threats to Birds and Human Health, Assessment the Relative Frequency of Pathogenic Fungi in Ornamental Bird Feces - Mirhosseini, Zahra; Khosravi, Alireza (Journal of Poultry Sciences and Avian Diseases, 2023)
Due to the high concentrations of nitrogen compounds and nutrients present in bird droppings, bird droppings provide fertile media for the growth and spread of various disease-causing microorganisms. Understanding the prevalence of these significant pathogenic fungi in pet birds’ feces is crucial for effective disease prevention and management. Culture and molecular tests are the most common tests for fungal infections. In the present study, 126 fecal samples were taken from different species of birds’ Psittacine, Passeriformes, and Columbiformes. The total fungal infection frequency was 83 (65.87%). Among the positive samples, 83 (71.55%) were filamentous fungi, and 33 (28.44%) were yeasts. Aspergillus flavus, Candida albicans, and Cryptococcus neoformans are the most important pathogens that were found in this study, with frequency of 34 (29.31%), 12 (10.34%), and 2 (1.72%), respectively. Since it is possible to isolate and identify potentially pathogenic fungi and molds for humans, this research and investigation is even more valuable. Therefore, examining and finding hygienic solutions for this issue will be particularly important.